1992
DOI: 10.1071/ea9920421
|View full text |Cite
|
Sign up to set email alerts
|

Management of highly fecund ewe types and their lambs for 8-monthly lambing. 1. Effect of lamb weaning age on ewe reproductive activity in spring

Abstract: The spring reproductive activity of ewes following a late winter lambing, and varying duration of suckling or lamb weaning age of 6-13 weeks, was investigated in 321 Booroola Merino x Dorset (BD) and 543 Trangie Fertility Merino x Dorset (TD) ewe records over 2 years and 238 Border Leicester x Merino (BLM) ewes in the second year. The ewes were joined about 12 weeks post-partum in November for 6 weeks, following lambing in July-August to conform to an %-monthly lambing regime. In the first year, ewes were run … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…While mating lactating ewes has been shown to prolong postpartum intervals in some studies (Mallampati et al 1954;Pope et al 1989), in others (Cognie et al 1975;Pope et al 1989;Fogarty et al 1992), it has been reported to increase pregnancy rates, ovulation rates, or litter size. The current trial showed breeding suckling ewes did not enhance or adversely affect ovarian CL counts, oestrus activity, pregnancy rates or litter size in ewes bred 68-73 days postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…While mating lactating ewes has been shown to prolong postpartum intervals in some studies (Mallampati et al 1954;Pope et al 1989), in others (Cognie et al 1975;Pope et al 1989;Fogarty et al 1992), it has been reported to increase pregnancy rates, ovulation rates, or litter size. The current trial showed breeding suckling ewes did not enhance or adversely affect ovarian CL counts, oestrus activity, pregnancy rates or litter size in ewes bred 68-73 days postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Wallace et al (1989), trabalhando com ovelhas induzidas, concluíram que as gonadotrofinas não foram fatores limitantes à prenhez de ovelhas lactantes até 42 dias após o parto. Fogarty et al (1992) postularam que não há interferência da intensidade da mamada na atividade éstrica de ovelhas e que o fotoperíodo é o principal responsável pela sasonalidade reprodutiva dos ovinos (Chemineau et al, 1992;Mandiki et al, 1990). No entanto, Mitchell et al (1998) concluíram que entre os fatores inibidores da liberação de LH (hormônio luteinizante) após parto, se inclui a amamentação associada à demanda metabólica da lactação, nutrição inadequada e/ou condição corporal precária.…”
Section: R Bras Zootecunclassified
“…However, flushing with lupin grains significantly decreased the ovulatory response in ewes on a long-term low plane of nutrition (Oldham and Fisher, 1992). Fogarty et al (1992) observed a decline in estrous response and an increase in the interval from lambing to first estrus in flushed ewes of -0.2 % and 1.3 days, respectively per kg gain in live weight.…”
Section: Cohenmentioning
confidence: 85%